The Effect Of Tax Planning On Firm Value (Empirical Study Of Various Industrial Companies Listed On The Indonesia Stock Exchange) - Rika Mei Hayani Ginting; Tia Novira Sucipto; Mery Lani Purba; Suriadi Ramadan (Information Technology and Science (ITScience), 2020)
In order to reduce the tax burden that must be paid, many companies carry out tax management, which is a comprehensive effort made by the tax manager (tax manager) in a company or organization so that matters related to taxation of the company or organization can well managed, efficient, and economical, so as to provide maximum contribution to the company. This study aims to determine the effect of tax planning on firm value. The sampling technique used is purposive sampling, the final sample size is 69 companies of various industries listed on the Stock Exchange. Indonesia 2016-2018. The analysis method used is simple linear regression analysis of panel data using SPSS 24.00. Based on the research results, it shows that tax planning has no and insignificant effect on firm value. It is recommended for further research if you want to follow up on tax planning and company value or with a similar research topic, it can be expected to add other variables, such as the profitability variable. Management is expected to be able to minimize its tax burden every year, because high tax burdens will have an impact on reducing profits.